2001
DOI: 10.1097/00006534-200111000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Facial Infiltrating Lipomatosis

Abstract: Facial infiltrating lipomatosis is a rare congenital disorder in which mature lipocytes invade adjacent tissue. The phenotypic features include soft-tissue and skeletal hypertrophy, premature dental eruption, and regional macrodontia. There is a high risk for regrowth after resection that is, perforce, subtotal. The etiology, natural history, optimal management, and relationship to other disorders of fatty overgrowth are unclear. In this study, the clinical features, radiographic findings, histopathology, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 33 publications
2
85
0
Order By: Relevance
“…Rare forms of human WAT dystrophies, such as Köbberling-Dunnigan syndrome (Anderson et al, 1999;Jackson et al, 1998;Peters et al, 1998) and congenital infiltrating lipomatosis of the face (D'Souza et al, 2014;Padwa and Mulliken, 2001;Urs et al, 2013), suggest different origins for subcutaneous adipocytes in the lower versus upper body part (Lemos et al, 2012;Sanchez-Gurmaches and Guertin, 2014a). To this end, lineage tracing by expressing the Cre protein (which causes DNA recombination) under the control of the neural crest marker Sox10 (SRY-related HMGbox 10) showed that adipocytes in the head and neck, but not trunk pgWAT and SAT, develop from the neuroectoderm (Billon et al, 2007).…”
Section: Subcutaneous and Visceral Adipocytes Have Different Developmmentioning
confidence: 99%
“…Rare forms of human WAT dystrophies, such as Köbberling-Dunnigan syndrome (Anderson et al, 1999;Jackson et al, 1998;Peters et al, 1998) and congenital infiltrating lipomatosis of the face (D'Souza et al, 2014;Padwa and Mulliken, 2001;Urs et al, 2013), suggest different origins for subcutaneous adipocytes in the lower versus upper body part (Lemos et al, 2012;Sanchez-Gurmaches and Guertin, 2014a). To this end, lineage tracing by expressing the Cre protein (which causes DNA recombination) under the control of the neural crest marker Sox10 (SRY-related HMGbox 10) showed that adipocytes in the head and neck, but not trunk pgWAT and SAT, develop from the neuroectoderm (Billon et al, 2007).…”
Section: Subcutaneous and Visceral Adipocytes Have Different Developmmentioning
confidence: 99%
“…While the mesoderm has long been considered the only source of WAT, certain forms of WAT dystrophies, such as congenital infiltrating lipomatosis of the face (CIL-F) [6,7] and the Dunnigan-Kobberling syndrome [8] suggest the existence of different cellular mechanisms for cephalic versus trunk and limb adipogenesis. Recently, others and we have reported the existence of a population of mesenchymal progenitors residing in both WAT and skeletal muscle that contains virtually all the adipogenic activity of both tissues [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…8 High signal intensity (isointense to fat) of the lesion on T 1 and T 2 weighted images (hypointense on fat suppressed images) in young patients is diagnostic in the presence of typical clinical features, thus eliminating need for biopsy. 4,21 Facial nerve encasement and intracranial/cerebral abnormalities (ipsilateral hemimegalencephaly, asymmetric ventricular-sylvian fissure dilatation, arachnoid cyst, cerebellopontine angle lipoma) can also be seen on MRI. [22][23][24] However, MRI features are not always reliable to differentiate CIL-F from well-differentiated liposarcomas.…”
Section: Discussionmentioning
confidence: 99%